From Passion to Profit: Navigating the Challenges of Scaling a Fashion Business in India - M A, Noushija (Global journal of Business and Integral Security, 2024)
The Indian fashion industry blends traditional craftsmanship and modern innovation. It has established itself as a significant player in the global fashion scene. This study explores the current state of fashion entrepreneurship in India, highlighting the industry’s challenges and opportunities. The study examines the technological advancements that have revolutionized the industry, including e-commerce, 3D printing, and AI-based marketing strategies. While these innovations offer new opportunities for market expansion and customer engagement, they also introduce challenges regarding rapidly changing consumer expectations and the need for continuous adaptation. Sustainability is a critical theme within the industry. Indian fashion businesses must integrate sustainable practices throughout their supply chains in response to increasing global consciousness about environmental and ethical practices. This shift is necessary to meet consumer demand and ensure long-term sustainability and compliance with international standards. Education also plays a significant role in shaping the future of fashion entrepreneurship. The study highlights the gaps in the current educational systems that fail to align with industry needs. It advocates for an updated curriculum with comprehensive training in digital skills, business management, and sustainable practices, which is crucial for nurturing a new generation of fashion entrepreneurs. The study also highlights the importance of supportive governmental policies and robust infrastructure to facilitate growth and innovation in the sector. Effective policy measures and a conducive business environment are essential for overcoming obstacles to finance, regulation, and international expansion. In conclusion, the Indian fashion industry has significant potential for growth and global influence. To achieve this, a concerted effort must be made to leverage technological innovations, embrace sustainability, enhance educational offerings, and foster a supportive policy environment. This comprehensive analysis provides actionable insights for industry stakeholders to capitalize on the opportunities within this vibrant industry.